Such quiet girls eaudiobook - Ihli, Noelle (Simon Maverick, 2025)
Ten children, abducted in broad daylight—and buried alive. Sage and her sister won't make it home from school today. Neither will the other children on Bus 315. But that's only the beginning of the nightmare. New bus driver Jessa blames herself for what happened. She couldn't protect the kids she was supposed to deliver to daycare, just like she couldn't protect her own daughter three years ago. But this time, everything will be different. It has to be. Trapped in a shipping container buried twenty feet underground, Jessa and the children do their best to stay calm. The kidnappers insist that if everyone behaves, they'll be freed when the ransom is paid. But Sage isn't sure they'll last that long. Neither is Jessa. It's dark and cramped, and with every passing minute it's getting harder to breathe. With time—and air—running thin, Jessa and the children must find a way to outsmart their captors, or face an unthinkable fate. Such Quiet Girls was inspired by actual events.